ADSORPSI ION KADMIUM(II) DARI LARUTANNYA MENGGUNAKAN BIOMASSA AKAR DAN BATANG KANGKUNG AIR (Ipomoea aquatica Forks) (Adsorption of Cadmium(II) Ion from its Solution by Using Biomass of Roots and Stems’ Water Spinach (Ipomoea Aquatic Forsk)) - Suhud, Iffatunniswah; Tiwow, Vanny M. A.; Hamzah, Baharuddin (Universitas Tadulako, 2012)
The research has been conducted on the adsorption of cadmium(II) ion from its solution by using biomassa roots and stems of water spinach (Ipomoea Aquatic Forsk). Theaim of the research was to determine optimum pH and concentration of cadmium(II) metal adsorbed by biomass root and stems of water spinach. The method used this study was laboratory experiments with 0.1 grams of roots and stems of water spinach powder as adsorbent and 25 mL of the cadmium(II) solution. The variation of pH was 1, 2.3, 4.5, 6.7, and 8, while the concentration was 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, and 700 ppm. Determination of cadmium(II) ion adsorbed by the adsorbent has been performed using atomic adsorption spectrophotometer (AAS). The measurement showed that the optimum pH of cadmium(II) ion adsorbed by the root of water spinach was at pH 4, and by the stems was at pH 3. While the optimum concentration of metal cadmium(II) solution adsorbed by the biomass of roots and stems of water spinach was 600 ppm, the same as the adsorption powerof 91.862 mg/g for root and 91.118 mg/g for stems respectively.